Speculative Bubbles in Urban Housing Markets in Germany - Konstantin Kholodilin; Claus Michelsen; Dirk Ulbricht (European Regional Science Association (ERSA), 2015)
In the light of the unconventional monetary policies conducted by the majority of large central banks around the world, there is an intense debate about their potential impact on the prices of capital assets. Particularly in Germany, skepticism about the sustainability of the recent policy by the European Central Bank is widely spread and concerns about the emergence of a speculative price bubble are raised. However, studies on bubbles in house prices are scarce and provide mixed results. Moreover, the evidence on German property prices is either based on national indices, which are neglecting city-level heterogeneity, or based on a non-representative sample of cities, or refers to a time period that is relatively short. The present study analyzes a comprehensive data set covering 127 large German cities over the last 20 years. Using state-of-the-art methodology we test for speculative bubbles both at a national and at the city level. Furthermore, we apply two new testing approaches: panel data and principal components versions of Chow type explosive root tests. In addition, we use a more precise definition of a speculative bubble: We define price movements as bubbles when explosive growth of prices is not supported by explosive increases of rents. We find evidence for explosive price increases in many cities, especially for newly built housing. However, only in some urban housing markets, prices decouple from their fundamental values as represented by rents. On the national level, no speculative price movements could be detected. Overall, our findings indicate that the threat of a speculative price bubble in the German housing market is moderate. While we find first evidence for speculative bubbles in selected urban markets, our results indicate that the German housing market overall still appears to be in good condition. Only the small market segment of newly built apartments is affected by potentially speculative investment behavior. Indeed, when accumulated over the period 2009-2013, the newly built housing makes up only 2.2% of the housing stock in 2013. Our results are largely in line with the assessment of most housing market analysts who find that the German housing market is quite stable. However, while most discussants argue that there is no need to worry at all, we conclude that decision makers are well advised to have a close eye on the housing market and to keep track of regional market developments. While it is true that unlike in Spain or the United States, the boom in the German housing market is not credit driven on aggregate, this does not necessarily mean that housing lending on the regional level has not increased substantially.
Keywords: C21; C23; C53; 330; housing prices; speculative bubble; explosive root; German cities